2016
DOI: 10.1186/s12882-016-0397-1
|View full text |Cite
|
Sign up to set email alerts
|

Association of peripheral arterial disease with all-cause and cardiovascular mortality in hemodialysis patients: a meta-analysis

Abstract: BackgroundRecent studies have shown an association between peripheral arterial disease (PAD) and increased risk of mortality in hemodialysis (HD) patients; however, the estimates vary widely and are inconsistent. It is necessary to elucidate the degree of mortality risk for PAD patients in HD population.MethodsPubMed, EMBASE, Web of Science and Cochrane Library (from inception to September 4th, 2016) were systematically searched for cohort studies assessing the association between PAD and mortality in HD patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 39 publications
3
20
0
1
Order By: Relevance
“…Lower Kt/V values were observed among patients in the PAD group, which is consistent with the findings from other studies [11, 25]. These findings might help explain why some uremic toxins that are not removed by dialysis, for example, dimethylarginine, accumulates, damages endothelial cells, and causes atherogenesis [19].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Lower Kt/V values were observed among patients in the PAD group, which is consistent with the findings from other studies [11, 25]. These findings might help explain why some uremic toxins that are not removed by dialysis, for example, dimethylarginine, accumulates, damages endothelial cells, and causes atherogenesis [19].…”
Section: Discussionsupporting
confidence: 90%
“…Intermittent claudication is the classic and most striking symptom associated with PAD, and it is relatively rare in the general population and in patients on HD [5, 19]. Therefore, intermittent claudication alone is not a reliable criterion for a diagnosis of PAD [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, vascular complications like steal syndrome or trash foot may be a threat to the vascular challenging transplant candidate . As a third reason, patients with VC are considered to have a limited life expectancy due to cardiovascular comorbidities, leading to a high perioperative mortality risk and limiting 5‐year patient survival to 35% . Due to organ shortage, it might not be ethical to perform a deceased donor KTx in patients with such a limited life expectancy.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to diagnose PAD in HD patients because the prevalence of PAD in such patients (around 26%) was found to be much higher than in the general population (3–10%) . In addition, a recent meta‐analysis revealed that PAD was positively correlated to cardiovascular disease and all‐cause mortality in HD patients .…”
mentioning
confidence: 99%